2012
DOI: 10.1590/s0037-86822012000200018
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-rich high-molecular-mass antigens are strongly recognized during experimental Histoplasma capsulatum infection

Abstract: INTRODUCTION: During histoplasmosis, Histoplasma capsulatum soluble antigens (CFAg) can be naturally released by yeast cells. Because CFAg can be specifically targeted during infection, in the present study we investigated CFAg release in experimental murine histoplasmosis, and evaluated the host humoral immune response against high-molecular-mass antigens (hMMAg. >150 kDa), the more immunogenic CFAg fraction. METHODS: Mice were infected with 2.2x10(4) H. capsulatum IMT/HC128 yeast cells. The solubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…These antigens competed with actual fungal surface antigens in antibody formation and recognition. So, as with other components of the immune response, this pathogen may have escape mechanisms against antibodies as well (Tristão et al 2012). However, disease modifying monoclonal antibodies (mAb) have been described and include antibodies to cell surface displayed histone 2B (Nosanchuk et al 2003;Shi et al 2008), M antigen (Guimarães et al 2008;Nosanchuk et al 2012), and heat shock protein 60 (Guimarães et al 2009(Guimarães et al , 2011a.…”
Section: Adaptive Immune Response Granuloma Formation and Reactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…These antigens competed with actual fungal surface antigens in antibody formation and recognition. So, as with other components of the immune response, this pathogen may have escape mechanisms against antibodies as well (Tristão et al 2012). However, disease modifying monoclonal antibodies (mAb) have been described and include antibodies to cell surface displayed histone 2B (Nosanchuk et al 2003;Shi et al 2008), M antigen (Guimarães et al 2008;Nosanchuk et al 2012), and heat shock protein 60 (Guimarães et al 2009(Guimarães et al , 2011a.…”
Section: Adaptive Immune Response Granuloma Formation and Reactivationmentioning
confidence: 99%
“…Cytotoxic to pathogen Further propagate the immune response to eventually trap the pathogen within a granuloma Utilizes macrophages as a sanctuary Reactivates with changes to the host's immune status (Allen and Deepe 2006;Heninger et al 2006;Tristão et al 2012;Shi et al 2008;Nosanchuk et al 2003) a Sample references provided, please see text for full list of references and details on each topic…”
Section: Figmentioning
confidence: 99%
“…The usual immune response to H. capsulatum begins in the lung with the uptake of the fungus by resident AMs that are essential cells for clearing microorganisms by phagocytosis and intracellular killing (29). In addition, it has been demonstrated that H. capsulatum induces a humoral immune response and leads to production of circulating immune complexes (34). Since a humoral response is enhanced during the course of infection (34), it may be relevant in the setting of reinfection, particularly in endemic areas.…”
Section: In Vitro Ams Phagocytized Ops-h Capsulatum More Efficientlymentioning
confidence: 99%
“…In addition, it has been demonstrated that H. capsulatum induces a humoral immune response and leads to production of circulating immune complexes (34). Since a humoral response is enhanced during the course of infection (34), it may be relevant in the setting of reinfection, particularly in endemic areas. Therefore, we first investigated whether resident AMs produce PGD 2 and PGE 2 after in vitro infection with nonopsonized (H. capsulatum) or with specific IS-opsonized H. capsulatum (Ops-H. capsulatum).…”
Section: In Vitro Ams Phagocytized Ops-h Capsulatum More Efficientlymentioning
confidence: 99%
“…The yeast cells of P. brasiliensis strain Pb-18, isolated from a human patient (IFM 41621), corresponding to P. brasiliensis sensu stricto [6], that of H. capsulatum IMT/HC12 [14] isolated from a Peruvian patient, and A. karlae IFM 55165 isolated from a cutaneous lesion of a cat [15] were cultured on 1% yeast extract (Becton, Dickinson and Company, Sparks, MD, USA; BD) and 2% dextrose (Wako) added to brain heart infusion agar (BD) slants at 35 • C for 5 days. The slants were fixed with 70% ethanol for 48 h, washed 3 times with distilled water with a centrifuge at 1710× g for 5 min, suspended in distilled water for approximately 10% of the volume, and stored in a refrigerator at 4 • C.…”
Section: Fungal Cells Used As Antigensmentioning
confidence: 99%